Tasks, The Implementation of Which Will Ensure the Food Security of the Republic of Uzbekistan - Abdrashitova Elena Vladimirovna (Zien Journals, 2023)
The article tells about the new agrarian policy in the Republic of Uzbekistan, about new approaches to financing the developing agro-industrial complex. Timely state reforms and strategic planning in the field of attracting investments in the agrarian sector of the Republic.
Keywords: greenhouses; vegetable products; agro-industrial complex; agro-food market